Teen Choices, an Online Stage-Based Program for Healthy, Nonviolent Relationships: Development and Feasibility Trial - Levesque, Deborah A. (J Sch Violence, 2016)
This paper describes the theoretical foundation, development, and feasibility testing of an online, evidence-based intervention for teen dating violence prevention designed for dissemination. Teen Choices: A Program for Healthy, Non-Violent Relationships relies on the Transtheoretical Model of Behavior Change and expert system technology to deliver assessments and feedback matched to stage of change for using healthy relationship skills. The program also tailors feedback to dating status, risk level, and other key characteristics. Ninety-nine students from high schools in Tennessee and Rhode Island completed a Teen Choices session and 97 completed an 11-item acceptability evaluation. 100% of participants completed the intervention session as intended. Evaluations of the program were favorable. For example, 88.7% agreed the program feedback was easy to understand, and 86.7% agreed that the program could help people develop healthier relationships. Findings provide encouraging evidence of the acceptability and feasibility of this approach to dating violence prevention.